Fatores genéticos e de meio no intervalo de partos de caprinos leiteiros - Goncalves, H. C. (1997)
The kidding intervals (IDP) of dairy goats raised in Southeastern Brazil were studied to quantify the influence of environmental factors and to estimate genetic parameters by means of least squares (MMQ) and restricted maximum likelihood (REML). The data analyzed were obtained from five farms and three breeds (Alpine, Saanen, and Toggenburg). The overall mean and standard error of IDP, as estimated by MMQ, were 339 +/- 12.70 days. The interaction of year x season of parturition influenced IDP. In two of the years studied, goats kidding at the end of the kidding season showed a shorter IDP when compared to those that were kidding after the end of the season. A quadratic trend of IDP over years was observed across the three kidding periods. For the three seasons. IDP increased from 1986 until mid-1989 and decreased thereafter. The heritability and repeatability of IDP, as estimated by MMQ and REML, were: 0.046 +/- 0.071 and 0.103 +/- 0.043, and 0.00026 and 0.08411, respectively. These estimates indicate that little genetic gain can be expected from selection for this trait.